Determination of the most appropriate site selection of wind power plants based Geographic Information System and Multi-Criteria Decision-Making approach in Develi, Turkey - Genç, Mustafa Serdar (International Journal of Sustainable Energy Planning and Management, 2021)
Wind power has major benefits including providing for an increasing energy demand while tackling climate change problems. Detailed planning processes such as technical, social, environmental, various agents, and political concerns are essential for the development of wind energy projects. The objective of the present study is to develop a visualization that combines Geographic Information System (GIS) and Multi-Criteria Decision Making (MCDM) and implementation for Kayseri, Develi in Turkey as a case study. For the analyzes, CORINE CLC 2000 and other data sources were employed for data acquisition to unlock fragmented and hidden onshore data resources and to facilitate investment in sustainable coastal and inland activities. Several factors were determined in the wind power plant installations such as wind potential, roads, water sources, and these factors were analyzed based on their buffer zones. After detailed analyses, sites near the Havadan (7.87 MW) and Kulpak (9.22 MW) villages were found to be the most suitable locations for the installation of a potential onshore wind farm. The method suggested in this study can be used to analyze the suitability of any region at the regional level for onshore wind power plant and the results of the study can be used to develop based on public perception, renewable energy policies, energy political rules.